The OECD's development assistance committee and German development cooperation: a relationship under scrutiny - Guido Ashoff (Deutsches Institut für Entwicklungspolitik (DIE), 2000)
The OECD's Development Assistance Committee (DAC) is a coordinating body of the major bilateral donors which seeks to improve the effectiveness of development cooperation. The DAC's work focuses on three areas: (1) the setting of quality standards for development cooperation and the uniform recording of resource flows and aid performance, (2) policy coordination through the establishment of guidelines for important areas of development cooperation and (3) periodic reviews of the members' aid policies and programmes in the light of the common standards and guidelines (aid reviews).Some criticism of the DAC emerged from the German development cooperation community in the past. The two most important criticisms were that (1) the DAC was exceeding its mandate by claiming to implement a strategy of its own, which was formulated in the 1996 document “Shaping the 21st Century: The Contribution of Development Cooperation” (“S 21”); (2) the DAC had expanded its work programme too far and was neglecting its core tasks.Against this background, the Federal Ministry for Economic Cooperation and Development (BMZ) commissioned the GDI to undertake a study (Ashoff 2000), which considered the following aspects among others: (1) assessment and use of DAC results by the German aid system, (2) Germany's influence on the profile of the DAC's work, (3) relevance of the German criticism levelled at the DAC and (4) recommendations for German development cooperation. The most important findings are: The DAC has set a number of standards (definition of official development assistance/ODA, recommendations on the terms and conditions of aid, list of recipient countries, statistical reporting directives, aid-tying rules, anti-corruption clause, principles for the evaluation of development assistance), which Germany has acknowledged are important. With only a few qualifications, the DAC's policy guidelines are rated highly by the BMZ and the two most important executing agencies in German development cooperation, the German Agency for Technical Cooperation (GTZ) and the Bank for Reconstruction (KfW). However, they are not yet being used in German development cooperation as systematically as they should be. German development cooperation was reviewed by the DAC on three occasions in the 1990s. The resulting review reports contain clear positive and critical statements and recommendations. Given the DAC's rank as an internationally experienced and independent review body and the plain statements they make, the DAC's review reports, which have been published since 1994, are important documents that should be used exhaustively by the German development cooperation system internally, for discussions with Parliament and other government departments and in public relations work. The DAC is a forum on whose work Germany has been able to make a major impression with competent and committed contributions and which therefore gives Germany a chance to bring clear influence to bear on the donors' policy coordination. Successful involvement in the DAC along these lines, however, requires a considerable commitment of manpower and, in some respects, financial resources. The German development cooperation community should therefore decide what issues it intends to pursue in the DAC in the future and agree on the aim, nature and scale of its involvement. In “S 21” all the DAC members have pledged to help achieve seven quantified development objectives (“output targets”) with their development cooperation. The criticism referred to above is right to claim that “S 21” is not a DAC strategy but a declaration of intent, the implementation of which cannot be prescribed by the DAC, but is a matter for the DAC members and their partner countries. On the other hand, Germany should not only commit itself in principle to “S 21” and the output targets but also see the latter as additional guides in the planning of development cooperation measures. With cuts in funding and staff in the DAC Secretariat and the range of subjects covered by the DAC's work so wide, the danger is that the DAC will neglect its core functions. New issues should therefore be considered in the DAC only if the core tasks are being performed, the new issues attract broad interest among the DAC members, the aim is, where possible, to produce common guidelines and the DAC Secretariat has sufficient capacity to assist the DAC in its work.
Keywords: 330